PURIFIKASI DALAM PENGAJIAN, DAPAT MENGGALI KEDALAMAN ILMU DENGAN KETULUSAN HATI - Nufika Salsa Y (Tajdida: Jurnal Pemikiran dan Gerakan Muhammadiyah, 2022)
In Arabic the recitation is called at-ta'llimu which comes from the word ta'allama yata'alliiman which means learning. Meanwhile, the meaning of recitation itself can mean learning knowledge with a pious or knowledgeable person and has its own worship value for every Muslim. Meanwhile, linguistically the word recitation comes from the basic word "kaji" which means lesson (especially in matters of religion), then recitation is: (1) teaching and teaching, (2) reading the Qur'an. The word recitation is formed with the prefix "pe" and the ending "an" which has two meanings: first as a verb which means teaching, namely the teaching of Islamic religious sciences, and secondly as a noun denoting a place, namely a place to carry out Islamic religious teachings. which in its use many terms are used, as in today's society it is known as the Quranic assembly. This study discusses the purification or purification of Islamic teachings from the point of view of recitation. Purification in recitation refers to spiritual and moral development which involves sincerity, sincere intentions, and awareness of the values of truth. Thus, there will be self-actualization so that it can be reflected in the real life of all Muslims. Rasulullah SAW said: "This matter (namely Islam) will spread to all directions that are penetrated by night and day. Allah will not allow a single house, neither building nor hut, but Islam will enter it so that it can glorify the noble religion and humiliate the lowly religion. What is glorified is Islam and what is humiliated is disbelief